2020
DOI: 10.1134/s1069351320030039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seismic Waves in Water Level Changes in a Well: Empirical Data and Models

Abstract: The high-precision water level measurements with a sampling interval of 5-10 min were carried out in 1996-2017 in the YuZ-5 well, Kamchatka. In the obtained time series, water level variations caused by the passage of seismic waves (hydrogeoseismic variations-HGSV) during 19 earthquakes with М w = 6.8-9.1 which occurred at epicentral distances of 80-14.6 thousand km are revealed. Based on the HGSV morphological features, four main types of these variations are distinguished: oscillations (I); short (up to tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The e values were estimated by the formula logd e 0.48M w −0.33loge−1.4 (Wang, 2007;Wang and Chia, 2008) and used to evaluate the range of e variations for the earthquakes preceded by the HGPs in the wells of the Kamchatka Peninsula. Previously in (Wang, 2007;Wang and Chia, 2008;Wang and Manga, 2010;Kopylova and Boldina, 2020), the e values were applied to assess co-and postseismic phenomena in ground-and surface waters. In this work, the e values are used to assess the possible seismic impact of earthquake in the observation area with manifestations of hydrogeological precursors.…”
Section: Relationship Between Hydrogeological Precursors and Earthquamentioning
confidence: 99%
“…The e values were estimated by the formula logd e 0.48M w −0.33loge−1.4 (Wang, 2007;Wang and Chia, 2008) and used to evaluate the range of e variations for the earthquakes preceded by the HGPs in the wells of the Kamchatka Peninsula. Previously in (Wang, 2007;Wang and Chia, 2008;Wang and Manga, 2010;Kopylova and Boldina, 2020), the e values were applied to assess co-and postseismic phenomena in ground-and surface waters. In this work, the e values are used to assess the possible seismic impact of earthquake in the observation area with manifestations of hydrogeological precursors.…”
Section: Relationship Between Hydrogeological Precursors and Earthquamentioning
confidence: 99%
“…Figure 5 from paper [2] demonstrates the relationship between preseismic hydrogeochemical anomalies and magnitude and epicentral distance to wells of subsequent earthquakes. Distribution of specific density of seismic energy e [9,11,22,23] depending on earthquake parameters also shows in Figure 5. The e value is considered as a parameter of earthquake impact in area of a well with preseismic hydrogeochemical anomaly.…”
Section: Manifestation Of Hydrogeochemical Anomaliesmentioning
confidence: 88%
“…[20]. (ii) -e values were estimated by the formula logd e = 0.48M w − 0.33loge − 1.4 [2,[21][22][23]. (iii) -Medvedev-Sponheuer-Karnik scale, also known as 12-points MSK-64, is a macroseismic intensity scale used for evaluating shaking of Earth's surface based on observed effects in the earthquake area; the values of points are given for Petropavlovsk-Kamchatsky city.…”
Section: Introductionmentioning
confidence: 99%
“…The results of such studies were summarized in monographs [1,2]. In these monographs and in many other works [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], it was shown that during observations in piezometric wells equipped with level gauges or pressure sensors, various changes in the groundwater level and pressure were detected, mainly influenced by the seismic waves from the earthquakes. To a lesser degree, such studies investigated the changes in the groundwater pressure before the earthquakes (hydrogeodynamic precursors, HPs) as well as the effects of changes in the static stress state of water-bearing rocks during the ruptures in the earthquake sources (coseismic effects, CSEs).…”
Section: Introductionmentioning
confidence: 98%